Interview 3 - Abubakari, Yushawu
This file contains the interview notes with Shatter Corolla. Shatter Corolla (Pseudonymize) is 32 years old, married with 3 children. He has been in the scamming industry for 7 years. Shatter Corolla lives in this house with his family. He is a leader in the scamming industry. While he has other scammers working under him, he doesn’t have anybody he is working for. But he do collaborate with some scammers in Nigeria. The interview took place in his house.